Heading for the scene of the crash : the cultural analysis of America - Drummond, Lee, 1944- (Loose can(n)ons, 2018)
American anthropologists have long advocated cultural anthropology as a tool for cultural critique, yet seldom has that approach been employed in discussions of major events and cultural productions that impact the lives of tens of millions of Americans. This collection of essays aims to refashion cultural analysis into a hard-edged tool for the study of American society and culture, addressing topics including the 9/11 terrorist attacks, abortion, sports doping, and the Jonestown massacre-suicides. Grounded in the thought of Friedrich Nietzsche, the essays advance an inquiry into the nature of culture in American society.